2021
DOI: 10.1021/acsomega.1c04142
|View full text |Cite
|
Sign up to set email alerts
|

Metal Exchange of ZIF-8 and ZIF-67 Nanoparticles with Fe(II) for Enhanced Photocatalytic Performance

Abstract: Zeolitic imidazolate frameworks (ZIFs), such as ZIF-8 and ZIF-67, were found to be efficient catalysts. However, ZIFs are not used much in photocatalysis due to their low photocatalytic activity for most reactions. The photocatalytic activity can be improved by modifying the framework by exchanging the Zn­(II) ions (ZIF-8) and Co­(II) ions (ZIF-67) with a more photocatalytically active metal­(II) ion to form an efficient bimetallic ZIF photocatalyst. Redox-active iron (Fe)-based materials are known to be highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The PXRD clearly shows that the peak intensity of the Fe‐ZIFs decreased slightly as compared to those of the parent ZIF‐8, suggesting the loss of crystallinity during the metal exchange from Zn 2+ to Fe 2+ , which might be due to the octahedral coordination of Fe (II) into tetrahedral coordination. [ 19 ] Furthermore, a noticeable transformation in color from white (ZIF‐8) to light brown (Fe‐ZIF‐8) was observed (insets of Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The PXRD clearly shows that the peak intensity of the Fe‐ZIFs decreased slightly as compared to those of the parent ZIF‐8, suggesting the loss of crystallinity during the metal exchange from Zn 2+ to Fe 2+ , which might be due to the octahedral coordination of Fe (II) into tetrahedral coordination. [ 19 ] Furthermore, a noticeable transformation in color from white (ZIF‐8) to light brown (Fe‐ZIF‐8) was observed (insets of Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Zeolitic imidazolate frameworks (ZIFs) are one representative subclass of metal organic frameworks (MOFs) and have been employed as catalysts for thermally driven CO 2 cycloaddition reaction. For instance, Park et al explored the catalytic potential of ZIF-90 for CO 2 cycloaddition with propylene oxide and found that a high yield (ca. 81%) of propylene carbonate was achievable at 8 h by ZIF-90 under 1.2 MPa CO 2 and 120 °C .…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at ∼995 and ∼1175 cm –1 were corresponding to CC–N twisting and C–N bending vibration, respectively. The peak at ∼1015 cm –1 belonged to C–H out-of-plane bending vibration of CH 3 . , Moreover, a broad absorption band at the range of 3200–2200 cm –1 indicated the existence of N–H stretching vibration due to protonated imidazole and the peak at ∼3400 cm –1 was associated with O–H stretching vibration. Additionally, the peak (1591 cm –1 ) with the highest relative intensity was attributed to CC/CN or CO stretching vibration due to the presence of conjugated structures in Hmim or H 3 BTC ligands . These results indicated that ZIF-8 frameworks with protonated imidazole structures have been formed (Figure ).…”
Section: Resultsmentioning
confidence: 98%